Influence of structural position on fracture networks in the Torridon Group, Achnashellach fold and thrust belt, NW Scotland. (May 2015) - Watkins, Hannah; Butler, Robert W.H.; Bond, Clare E.; Healy, Dave
Abstract: In fold-and-thrust belts rocks undergo deformation as fold geometries evolve. Deformation may be accommodated by brittle fracturing, which can vary depending on structural position. We use 2D forward modelling and 3D restorations to determine strain distributions throughout folds of the Achnashellach Culmination, Moine Thrust Belt, NW Scotland. Fracture data is taken from the Torridon Group; a thick, coarse grained fluviatile sandstone deposited during the Proterozoic. Modelling infers a correlation between strain and simple curvature; we use simple curvature to infer how structural position and strain control fracture attribute variations in a fold and thrust belt. In high curvature regions, such as forelimbs, fracture intensities are high and fractures are short and oriented parallel to fold hinges. In low curvature regions fractures have variable intensities and are longer. Fracture orientations in these regions are scattered and vary over short distances. These variations do not relate to strain; data suggests lithology may influence fracturing. The strain history of fold structures also influences fracturing; structures with longer deformation histories exhibit consistent fracture attributes due to moderate-high strain during folding, despite present day low curvature. This is in contrast to younger folds with similar curvatures but shorter deformation histories. We suggest in high strain regions fracturing is influenced by structural controls, whereas in low strain regions lithology becomes more important in influencing fracturing. Highlights: We use 2D forward modelling and 3D model restorations to predict strain in folds. We present field data for fracture intensity, orientation, length and distribution. Fracture attributes are consistent in high strain regions such as fold forelimbs. Fracture attributes are variable in low strain regions such as fold backlimbs. Lithological variations may influence fracturing where strain is low.